The study of epidemiological correlates of hypertension among the rural population of Mehsana district of North Gujarat region, India - Thakor, Nilesh; Nimbalkar, Pankaj B.; Joshi, Maulik D. (International Journal Of Community Medicine And Public Health, 2021)
Background: The changing lifestyle factors in rural population are associated with increase in hypertension. Objective was to find out the epidemiological correlates of hypertension among the rural population. Methods: This was cross sectional study and conducted in rural areas of Mehsana district of Gujarat during January 2019 to June 2019. People living rural areas were selected by stratified random sampling. They were screened for hypertension by JNC VII criteria using sphygmomanometer and detailed personal, past and family history was taken after written and informed consent. Data was entered in Microsoft excel and analysis was done using SPSS statistical package. Results: Out of total 602 subjects, 93 (15.4%) were hypertensive. Out of total 93 hypertensive subjects, 50 (53.8%) were females. A blood pressure category and gender difference were not statically significant (p=0.89). Out of 93 hypertensive subjects, 42 (45.2%) subjects were in the age group of ≥60 years. The difference between age groups and blood pressure category was significant (p<0.0001). Out of 93 hypertensive subjects’ majority 85 (91.4%) had negative tobacco history while only 8 (8.6%) consumed tobacco in any form. The tobacco history and blood pressure category were not significantly associated (p=0.211). Out of total 93 hypertensive subjects, 54 (58.1%) subjects were (≥25) body mass index (BMI). Categories of BMI and hypertension were extremely significantly associated (p<0.0001). Conclusions: Hypertension is significantly associated with age, socio economic class and BMI.